2014
DOI: 10.1254/jphs.13151fp
|View full text |Cite
|
Sign up to set email alerts
|

Tranilast Alleviates Endothelial Dysfunctions and Insulin Resistance via Preserving Glutathione Peroxidase 1 in Rats Fed a High-Fat Emulsion

Abstract: Abstract. We investigated the effects of treatment with tranilast on vascular and metabolic dysfunction induced by a high-fat emulsion intragastric administration. Wistar rats were randomized to receive water or high-fat emulsion with or without tranilast treatment (400 mg/kg per day) for 4 weeks. Insulin sensitivity was determined with a hyperinsulinemic-euglycemic clamp experiment and short insulin tolerance test. Vascular reactivity was evaluated using aortic rings in organ chambers. Glutathione peroxidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 60 publications
2
12
1
Order By: Relevance
“…We observed that, after preincubation with this drug, ACh-induced relaxation was decreased to a similar extent in both experimental conditions indicating that NO does not participate in the effect observed after preincubation with tranilast. This was confirmed by the fact that NO release, superoxide anion formation and vasodilator response to NO donor DEA-NO were not modified after preincubation with tranilast, similarly to reported in rat aorta [15]. All these results contrast with our previous results in superior mesenteric artery, where we observed decreases in neuronal NO and superoxide anion releases and an increase in the vasodilator response to DEA-NO after tranilast preincubation [14].…”
Section: Discussionsupporting
confidence: 91%
“…We observed that, after preincubation with this drug, ACh-induced relaxation was decreased to a similar extent in both experimental conditions indicating that NO does not participate in the effect observed after preincubation with tranilast. This was confirmed by the fact that NO release, superoxide anion formation and vasodilator response to NO donor DEA-NO were not modified after preincubation with tranilast, similarly to reported in rat aorta [15]. All these results contrast with our previous results in superior mesenteric artery, where we observed decreases in neuronal NO and superoxide anion releases and an increase in the vasodilator response to DEA-NO after tranilast preincubation [14].…”
Section: Discussionsupporting
confidence: 91%
“…Tranilast treatment (400 mg/kg per day for 4 weeks) prevented vascular dysfunction, insulin resistance, as well as increases in plasma glucose in highfat emulsion-treated rats. These effects were linked with preserving antioxidant enzyme GPX1 expression, eNOS activity and NO production, but reductions in H 2 O 2 accumulation alleviated oxidative damage and inflammation accordingly [151]. In addition, treatment with tranilast enhanced glucose uptake in pancreatic beta-cells and islets [152].…”
Section: Tranilast Against Diabetesmentioning
confidence: 98%
“…Tranilast was found to prevent the reduction in eNOS phosphorylation and activity, along with NO production, in the vascular tissues [151]. Nitric oxide synthase (iNOS) mRNA and protein expression, as well as the release of NO from N9 microglial cells, are inhibited when cells are exposed to tranilast [180].…”
Section: Nitric Oxide (No)mentioning
confidence: 99%
“…As ROS production is a common feature of the above described pathways [119, 164], chronic oxidative stress certainly plays a central role in the development of diabetes and diabetic complications [22, 165, 166]. Indeed, it has been reported that ROS can induce insulin resistance [74, 167], impair insulin synthesis [168], and impair beta cell insulin secretion [97, 169]. Additionally, oxidative stress biomarkers have been shown to be increased in individuals who exhibit insulin resistance [170173] or insulin secretion impairment [174177], indicating a positive correlation between oxidative stress and insulin resistance and insulin secretion impairment.…”
Section: Oxidative Stress Diabetes and Diabetic Complicationsmentioning
confidence: 99%